ANALISIS ATITTUDE TOWARDS THE ENVIRONMENT PADA SISWA KELAS IV SDN 2 PEMATANG PANGGANG - Desi Rosida; Masnunah; Sylvia Lara Syaflin (STKIP Subang, 2023)
Attitude can be seen as a condition within a person that is able to move that person to act or act with that feeling in response to various objects or situations that occur in their social environment. The purpose of this study was to determine the analysis of attitudes towards the environment in fourth grade students at SDN 2 Pematang Panggang. The method used is descriptive qualitative. The attitude towards the environment consists of 4 indicators: the first is always preserving the environment, the second is loving the neatness and cleanliness of the school, the third is participatory-based activities, the fourth is supporting greening. The data collection technique uses observation at the homeroom teacher for class IV SDN 2 Pematang Panggang, interviews with the homeroom teacher for class IV. and fourth grade students at SDN 2 Pematang Panggang, a questionnaire test which was distributed to 20 students and documentation in the form of photographs during the study. The results of distributing the questionnaire show that the results of the average student respondent are categorized as good with an average of 8.5. Analysis of the results of the questionnaire tests of 20 students who were divided into the first 2 categories, 10 students were very good and 10 students were good. IV has now increased from grade 1 and understands that attitudes towards the environment must be developed from an early age. Keywords: Analysis, Attitude Towards The Environment, Qualitative